2017
DOI: 10.21451/1984-3143-ar944
|View full text |Cite
|
Sign up to set email alerts
|

Effects of body condition score and daily milk yield on reproduction traits of Czech Fleckvieh cows

Abstract: The objective of this study was to evaluate the effects of body condition score (BCS) and daily milk yield (DMY) on reproductive characteristics of dairy cows. A total of 1249 records of Czech Fleckvieh cows raised at a private farm in Prague were enrolled. Dairy cows were grouped according to BCS (1 = ≤3.75, 2 = 4-4.25 and 3 = ≥ 4.50) and DMY groups (<20kg, 20-30 kg and >30kg). Number of inseminations per pregnancy (NI), days open (DO), service period (SP) and ovarian cyst (OC) cases were evaluated as reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
3
11
0
2
Order By: Relevance
“…The COD incidence was reported more in 4 th parity in a study conducted in Norwegian dairy cattle by Nelson et al [18] . Stadnik et al [19] reported that the group with BCS≤3.75 had lower ovarian cystic cases (8.98% animals), when compared with other BCS groups of cows with BCS 4 -4.25 (22.86 % of animals) and ≥4.50 (21.50% animals). Normally, excessive BCS is highly related to ovarian cystic cases [20] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The COD incidence was reported more in 4 th parity in a study conducted in Norwegian dairy cattle by Nelson et al [18] . Stadnik et al [19] reported that the group with BCS≤3.75 had lower ovarian cystic cases (8.98% animals), when compared with other BCS groups of cows with BCS 4 -4.25 (22.86 % of animals) and ≥4.50 (21.50% animals). Normally, excessive BCS is highly related to ovarian cystic cases [20] .…”
Section: Discussionmentioning
confidence: 98%
“…Especially over-conditioning may be referred to as weak fertility or nutrition programs in dairy farms. That's why preventing cows from high BCS should principally be considered to obtain fertile cows [19] . Further, body condition may be expected to fall if feed intake declines during periods of high heat and humidity [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Por tanto, un kilogramo de materia seca de ambos materiales presenta una concentración porcentual a favor del kikuyo de 5,69 % de ENL, 4,80 % NDT y 13,73 % de PC, que aporta más nutrimentos al animal; sin considerar el efecto sobre el consumo voluntario de alimento y el bienestar animal que presenten estas condiciones al generar periodos de estrés en el semoviente (Silanikove, 2000). Otras consideraciones que explican estas diferencias en producción, según el día de lactancia, se podrían asociar a la condición corporal (Stadnik et al, 2017), el número de lactancia y a la edad del animal que presentó cada animal al momento de la recolección de la información (Haworth et al, 2008), sumado al genotipo de los animales y la respuesta a la interacción con el ambiente, este último incluiría el manejo alimenticio y las condiciones ambientales que se registran en estos sistemas (Soydan y Kuran, 2017), como la variación de la temperatura y la humedad relativa.…”
Section: Discussionunclassified
“…The evaluation of production traits, reproduction traits and relation between each other in dairy cows shows authors in Slovakia (Bujko et al, 2019 andKasarda et al, 2020), Czech (Stadnik et al, 2018) Austria (Costa et al, 2019), Poland (Satoła et al, 2017), Romania (Cziszter et al, 2017;Han andBobiş, 2019), New Zealand (Sneddon et al, 2015) and other authors who have dealt with the similar areas of research.…”
Section: The Evaluation Of the Relationship Of Lactose To Production mentioning
confidence: 94%